2007
DOI: 10.1007/s10750-007-0606-9
|View full text |Cite
|
Sign up to set email alerts
|

Land use changes and associated environmental impacts on the Mediterranean shallow Lake Stymfalia, Greece

Abstract: Land cover and land use changes affect ecological landscape functions and processes. Land use changes mainly caused by human activities, is a common reason for wetlands degradation worldwide. Lake Stymfalia, located at Peloponnese, southern Greece, is an ancient wetland with a great ecological value. Lake Stymfalia has been severely degraded and transformed during the past 60 years due to agricultural activities in the surrounding areas and watercourses alterations. In this context, we investigated the land co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…It is well known that changes in land cover and land use affect ecological landscape functions and processes, which mean the erosion phenomena, are very strong; also the capacity of water retention of the eroded land is very scarce (Papastergiadou et al 2007;Wissman 2006).…”
Section: Land/water Interaction: Availability Of the Allocutions Orgamentioning
confidence: 99%
“…It is well known that changes in land cover and land use affect ecological landscape functions and processes, which mean the erosion phenomena, are very strong; also the capacity of water retention of the eroded land is very scarce (Papastergiadou et al 2007;Wissman 2006).…”
Section: Land/water Interaction: Availability Of the Allocutions Orgamentioning
confidence: 99%
“…Such effects are likely to lower water tables and affect water supply, especially in areas where water abstraction will be intensified in order to meet the growing demand for water [8]. Other examples from Greece showed that historical land cover/use changes of lakes and wetlands revealed a significant shrinkage of water surface and its replacement with other types of land cover, mainly cultivations [9][10][11]. Consequently, these land use changes combined with climate induced hydrologic alterations are expected to have a drastic effect on the ecology of freshwater lakes, including changes of the biotic communities, eutrophication enhancement, increase of turbidity and a shift to brackish or even saline conditions [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the settlement of macrophyte litter increases carbon storage, and also is responsible for increasing the sediment layer and accelerating lake terrestrialization [6,7]. Over the past decades, the terrestrialization of aquatic environments due to the deposition of macrophyte-related organic matters has attracted considerable attention [8,9]. Furthermore, accumulated organic matter also causes the depletion of oxygen and accelerates the production of greenhouse gases such as methane.…”
Section: Introductionmentioning
confidence: 99%